Peran Electronic Word Of Mouth Dalam Mempengaruhi Keputusan Berkunjung Ke Wisata Alam Taman Waru - Riyan Erwin Hidayat; Agus Alimuddin; Suhairi Suhairi; Dwi Nugroho (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2021)
Electronic word of mouth is part of a strategy to influence visiting decisions, maximizing the use of which can increase the number of visitors in Taman Waru nature tourism. the decision to visit Taman Waru natural tourism was not entirely based on electronic word of mouth. The purpose of this study is to try to complete the understanding of the role of electronic word of mouth in influencing the decision to visit Taman Waru nature tourism. Research conducted using qualitative methods, selecting informants by random sampling, the resulting data is presented in a descriptive form so that it is structured and has a high level of readability. It turns out that electronic word of mouth has an impact on the decision to visit through online reviews in the form of comments, which so far it is said that electronic word of mouth only displays interesting information on a product has no reason.